History of law and other humanities: views of the legal world across the time - Amorosi, Virginia (ed.) (Historia del Derecho, 2019)
The collection of thirty-five essays presented here examines the links forged through the ages between the realm of law and the expressions of the humanistic culture. The essays are organized into sections of ten chapters based around ten different themes. Two main perspectives emerged: in some articles the topic relates to the conventional approach of 'law and/in humanities' (iconography, literature, architecture, cinema, music), other articles are about more traditional connections between fields of knowledge (in particular, philosophy, political experiences, didactics). The variety of authorial nationalities gives the collection a multicultural character and the historiographical interpretation is the element that unites the collection, with a breadth of the chronological period goes from antiquity to the contemporary age. This project is the result of discussions that took place during the XXIII Forum of the Association of Young Legal Historians held in Naples in the spring of 2017.